Fatherhood and money : the experiences of unemployed fathers and their navigation of fatherhood in Soweto - Tyawa, Gugulethu (My University, 2017)
Despite the growing literature on fatherhood, the provider role enormously remains a role that defines fathers' masculinity and respective stature in society. However with unemployment on the rise, unemployed fathers are highly disadvantaged when it comes to fulfilling this role due to social construct and cultural influences. This study therefore aims to explore the experiences of unemployed fathers and their navigation of fatherhood in instances of this reality. Adopting the qualitative research approach, twelve (12) unemployed fathers residing in any township of Soweto were recruited using purposive and snowball sampling technique. Individual interviews were held with each participant and the interviews were recorded, transcribed and analysed using thematic analysis. The main finding drawn from the study was that unemployed fathers felt compelled to provide for their children and families even though they simply did not have the means to do so; eliciting clearly how much weight money has in the execution of fatherhood; therefore obscuring the many other roles unemployed fathers can fulfill. Key words: Unemployment, father, fatherhood, masculinity, money, navigate
A report study project presented to The Department of Social Work School of Human and Community Development Faculty of Humanities University of the Witwatersrand In partial fulfillment of the requirements for the degree Bachelor of Social Work